2023
DOI: 10.1007/s13205-023-03751-4
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-mediated amelioration of drought stress in plants: a systematic review

Harsha K. Chandrashekar,
Gunjan Singh,
Arya Kaniyassery
et al.

Abstract: Drought stress remains one of the most detrimental environmental constraints that hampers plant growth and development resulting in reduced yield and leading to economic losses. Studies have highlighted the beneficial role of carbon-based nanomaterials (NMs) such as multiwalled carbon nanotubes (MWNTs), single-walled carbon nanotubes (SWNTs), graphene, fullerene, and metal-based nanoparticles (NPs) (Ag, Au, Cu, Fe2O3, TiO2, and ZnO) in plants under unfavorable conditions such as drought. NPs help plants cope w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 93 publications
1
2
0
Order By: Relevance
“…Moreover, all of the NP treatments that were assessed in drought-stressed conditions showed an increase in biomass accumulation, whereas, in comparison to the control, the NP Ultra treatment proved to be the most effective. In this regard, similar findings have been reported in soybean research, where it was found that Fe, Cu, Co, and ZnO NP may increase plant tolerance to drought stress by promoting the expression of drought-related genes, such as GmWRKY27 , GmMYB118 , and GmMYB174 , involved in cell growth [ 83 , 84 ]. Cobalt is an essential nutrient for legumes since it is required for leghemoglobin synthesis and, thus, symbiotic nitrogen fixation.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, all of the NP treatments that were assessed in drought-stressed conditions showed an increase in biomass accumulation, whereas, in comparison to the control, the NP Ultra treatment proved to be the most effective. In this regard, similar findings have been reported in soybean research, where it was found that Fe, Cu, Co, and ZnO NP may increase plant tolerance to drought stress by promoting the expression of drought-related genes, such as GmWRKY27 , GmMYB118 , and GmMYB174 , involved in cell growth [ 83 , 84 ]. Cobalt is an essential nutrient for legumes since it is required for leghemoglobin synthesis and, thus, symbiotic nitrogen fixation.…”
Section: Discussionsupporting
confidence: 81%
“…Key factors influencing the extent of these changes include the chemical composition, size, concentration, surface coating, reactivity of the nanoparticles, treatment duration, application method, and the type of plant species or cultivar [ 7 , 36 , 37 ]. Growth parameters and content of photosynthetic pigments provide insight into how plants react to stress caused by nanoparticles [ 38 , 39 ]. Al-Huqail et al [ 40 ] found that silver nanoparticles have the potential to inhibit chlorophyll production in leaves, consequently impacting a plant's photosynthetic capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) ; Alharbi et al. (2023) and Chandrashekar et al. (2023) , PGPR with NPs increased the relative water content, stomatal conductance, chlorophyll, and carotenoids in plants.…”
Section: Synergistic Role Of Pgpr and Nanoparticles Enhancing Physiol...mentioning
confidence: 98%